2015
DOI: 10.1038/srep08810
|View full text |Cite
|
Sign up to set email alerts
|

Discrete Li-occupation versus pseudo-continuous Na-occupation and their relationship with structural change behaviors in Fe2(MoO4)3

Abstract: The key factors governing the single-phase or multi-phase structural change behaviors during the intercalation/deintercalation of guest ions have not been well studied and understood yet. Through systematic studies of orthorhombic Fe2(MoO4)3 electrode, two distinct guest ion occupation paths, namely discrete one for Li and pseudo-continuous one for Na, as well as their relationship with single-phase and two-phase modes for Na+ and Li+, respectively during the intercalation/deintercalation process have been dem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 35 publications
2
42
0
Order By: Relevance
“…24 All calculations used the PBEsol exchange-correlation functional. 25 To describe the strongly correlated Fe 3d electrons, we applied a Hubbard-type "+U" correction of Ud = 4.3 eV, using the rotationally invariant approach of Dudarev et al 26 This value of Ud = 4.3 eV was chosen for consistency with previous calculations of orthorhombic Li + -and Na + -inserted Fe2(MoO4)3 by Yue et al 15 who, in turn, selected this value from earlier calculations on LixFePO4. 27 A planewave cutoff of 550 eV was used, and all calculations were spin-polarized.…”
Section: Computationalmentioning
confidence: 99%
See 1 more Smart Citation
“…24 All calculations used the PBEsol exchange-correlation functional. 25 To describe the strongly correlated Fe 3d electrons, we applied a Hubbard-type "+U" correction of Ud = 4.3 eV, using the rotationally invariant approach of Dudarev et al 26 This value of Ud = 4.3 eV was chosen for consistency with previous calculations of orthorhombic Li + -and Na + -inserted Fe2(MoO4)3 by Yue et al 15 who, in turn, selected this value from earlier calculations on LixFePO4. 27 A planewave cutoff of 550 eV was used, and all calculations were spin-polarized.…”
Section: Computationalmentioning
confidence: 99%
“…13 Recent studies by Yue et al reported a two-phase structural change for Li + (de)insertion, but a single-phase process for Na + -intercalation in the high-temperature, orthorhombic (not monoclinic) polymorph of Fe2(MoO4)3. 15 To reconcile these various conflicting reports, it is crucial to understand the mechanism by which the structural framework transforms in order to accommodate the intercalation of guest ions.…”
Section: Introductionmentioning
confidence: 99%
“…A pair of FeO 6 octahedra is connected by three MoO 4 tetrahedra, forming a lantern-like motif, as shown in Figure b. This type of structure has large interstitial vacant sites and diffusion channels for guest ions. However, FMO has intrinsic poor performance in cycle life and rate capabilities because of its low conductivity. , Thus, considerable efforts have been made to improve its practical performance by developing synthetic and surface-coating methods. ,, On the other hand, recent work has studied the intercalation mechanism of FMO to understand an interesting difference in intercalation behavior between Li and Na ions, a two-phase reaction upon lithiation in contrast to a single-phase (solid-solution) reaction upon sodiation. , Such different behaviors have been known for decades; however, they are not yet well understood, particularly because of an unknown crystal structure for the sodiated phase, Na 2 Fe 2 ­(MoO 4 ) 3 (Na 2 FMO).…”
Section: Introductionmentioning
confidence: 99%
“… Monoclinic Fe 2 (MoO 4 ) 3 (FMO) shows distinct structural and electrochemical differences in the intercalation mechanism, depending on the guest ion. , FMO undergoes a single-phase reaction in a Na-ion cell, but a two-phase reaction in a Li-ion cell. Attempts to understand the difference in the mechanisms have been hindered by a lack of structural information on the fully sodiated phase Na 2 Fe 2 ­(MoO 4 ) 3 due to its structural complexity and the unavailability of a single crystal.…”
mentioning
confidence: 99%
“…Anti-NASICON-type Fe 2 (MO 4 ) 3 (where M = Mo or W) is an interesting intercalation electrode material owing to the robust structural topology created by large interstitial voids scattered throughout a 3D network of polyhedra. The intercalation of monovalent ions into the Mo analog has been previously studied in some detail. , Recently, we reported the mechanistic difference between Li + and Na + insertion and deinsertion into the monoclinic polymorph of Fe 2 (MoO 4 ) 3 . It was found that sufficient Li + intercalation produces a phase transformation to a monoclinic structure featuring ordered Li + positions.…”
Section: Introductionmentioning
confidence: 99%